IMPLEMENTASI E-ARSIP BEBAN KERJA DOSEN UNIVERSITAS ISLAM INDRAGIRI - Huda, Yusrol; Muni, Abdul (Indragiri Islamic University, 2023)
The development and advancement of information technology is currently running very fast, current technology has an impact on increasing effectiveness and efficiency in carrying out each job. reporting tri dharma activities carried out by lecturers, therefore the lecturer's workload must be distributed proportionally and measurably by utilizing the development of information technology. One of them is the Lecturer Workload E-Archive which can assist the Head of Study Program in finding out information on the workload borne by each lecturer. In the design of the Lecturer Workload E-Archive, Waterfall is a system development method that functions as a mechanism for identifying software, as well as UML (Unified Modeling Language) as modeling, and uses the PIECES method as a system analysis to facilitate researchers in building systems. Testing is carried out using Blackbox which plays a role in overcoming tests on the system software section and a questionnaire to determine system user satisfaction. With the Lecturer Workload E-Archive (BKD) the data is centralized so as to avoid duplication of data and make it easier to find and track information for lecturer assessment and fulfill the required accreditation documents